Association of preoperative smoking with the occurrence of postoperative pulmonary complications: A post hoc analysis of an observational study in 29 countries - Dorland, Galina; Saadat, W; van Meenen, David M P; Neto, Ary Serpa; Hiesmayr, Michael; Hollmann, Markus W; Mills, Gary H; Vidal Melo, Marcos F; Putensen, Christian; Schmid, Werner; Severgnini, Paolo; Wrigge, Hermann; et al. (Journal of clinical anesthesia, 2025)
INTRODUCTION: While smoking has been consistently identified as a significant contributor to postoperative complications, the existing literature on its association with postoperative pulmonary complications remains conflicting. AIM: We examined the association of preoperative smoking with the occurrence of postoperative pulmonary complications (PPCs). METHODS: Post hoc analysis of an observational study in 146 hospitals across 29 countries. We included patients at increased risk of PPCs, according to the Assess Respiratory Risk in Surgical Patients in Catalonia (ARISCAT) score (≥ 26 points). The primary endpoint was the occurrence of one or more predefined PPCs in the first five postoperative days, including unplanned postoperative need for supplementary oxygen, respiratory failure, unplanned need for invasive ventilation, ARDS, pneumonia and pneumothorax. Secondary endpoints included length of hospital stay and in-hospital mortality. We performed propensity score matching to correct for factors with a known association with postoperative outcomes. RESULTS: Out of 2632 patients, 531 (20.2 %) patients were smokers and 2102 (79.8 %) non-smokers. At five days after surgery, 101 (19.0 %) smokers versus 404 (19.2) non-smokers had developed one or more PPCs (P = 0.95). Respiratory failure was more common in smokers (5.1 %) than non-smokers (3.0 %) (P = 0.02), while rates of other PPCs like need for supplementary oxygen, invasive ventilation, ARDS, pneumonia, or pneumothorax did not differ between the groups. Length of hospital stay and mortality was not different between groups. Propensity score matching did not change the findings. CONCLUSION: The occurrence of PPCs in smokers is not different from non-smokers. FUNDING: This analysis was performed without additional funding. LAS VEGAS was partially funded and endorsed by the European Society of Anaesthesiology through their Clinical Trial Network and the Amsterdam University Medical Centers, Amsterdam, The Netherlands. REGISTRATION: LAS VEGAS was registered at Clinicaltrials.gov (NCT01601223). PRIOR PRESENTATION: Preliminary study results have been presented at the Euroanaesthesia 2024 International Congress, in Munich, Germany.
Keywords: senioři; kouření; Preoperative Period; Respiratory complications; Length of Stay; plicní nemoci; délka pobytu; Middle Aged; mužské pohlaví; Postoperative Complications; mortalita v nemocnicích; PPCs; Smoking; předoperační období; Lung Diseases; ženské pohlaví; Postoperative pulmonary complications; Humans; Intraoperative ventilation; Propensity Score; lidé středního věku; Hospital Mortality; tendenční skóre; rizikové faktory; Anaesthesia; Female; Aged; Risk Factors; Postoperative outcome; pooperační komplikace; lidé; Male